Five blueberry anthocyanins and their antioxidant, hypoglycemic, and hypolipidemic effects in vitro - Zhu, Chao-wei; Lü, Han; Du, Lan-lan; Li, Jing; Chen, Han; Zhao, Hui-fang; Wu, Wen-long; Chen, Jian; Li, Wei-lin (Frontiers in Nutrition, 2023)
The dual epidemic of obesity and diabetes mellitus is becoming an important worldwide public health issue. “Diabesity” is the term used to describe the combined detrimental health effects of both diabetes mellitus and obesity/overweight. Currently, food-derived bioactive compounds are suggested to alleviate diabesity. Blueberries are rich in bioactive anthocyanins, which is associated with the contribution on obesity and diabetes mellitus. However, the accurate active compounds and the underlying mechanism are still not clear. The objective of this study was to investigate the beneficial effects of blueberry anthocyanin on diabesity. Five anthocyanins (delphinidin-3-O-galactoside, delphinidin-3-O-glucoside, petunidin-3-O-galactoside, petunidin-3-O-glucoside, malvidin-3-O-galactoside) were isolated from rabbiteye blueberry (Vaccinium virgatum) cultivar ‘Garden blue’. All these anthocyanins exhibited oxygen radical absorbance capacity (ORAC), scavenging power of ABTS+ and DPPH free radical and inhibitory activity of α-glucosidase in vitro. Moreover, some compounds improved glucose uptake and attenuated lipid accumulation in high glucose and oleic acid treated HepG2 cells. All these results suggest that blueberry anthocyanins have potential antioxidant, hypoglycemic and hypolipidemic effects, which may benefit the treatment of diabesity.